Groundwater Depletion Embedded in Domestic Transfers and International Exports of the United States. Issue 2 (1st March 2020) - Gumidyala, Sajani; Ruess, Paul J.; Konar, Megan; Marston, Landon; Dalin, Carole; Wada, Yoshihide
Abstract: The United States plays a key role in global food security by producing and exporting agricultural products. Groundwater irrigation is increasingly important in agricultural production, nearly tripling since records began in 1950. Increased reliance on groundwater and prolonged unsustainable pumping of aquifers has led to groundwater depletion in many areas. In this study, we ask: How much groundwater depletion is embedded in the domestic transfers and international agricultural exports of the United States? How much do domestic and international agricultural commodity fluxes rely on unsustainable groundwater use? To address these questions, we quantify the amount of nonrenewable groundwater that is incorporated into agricultural commodities produced in the United States and transferred both within the country and exported internationally. We find that 26.3 km 3 of nonrenewable groundwater was transferred domestically in 2002 and 2.7 km 3 was sent abroad. In 2012, 34.8 km 3 was transferred domestically and 3.7 km 3 was exported. This indicates an increase of 32% in domestic transfers and 38% in international exports. In 2002, we find that 1, 491, 126 kt (340 billion USD) of agricultural products reliant on nonrenewable groundwater were domestically transferred, while 119, 048 kt (47 billion USD) were exported. In 2012, the mass transfer of agricultural goods reliant on unsustainable groundwater decreased, but their value in national and international supply chains increased by 54% and 31%, respectively. Our results underscore the importance of the long‐term risks posed to global agricultural supply chains from reliance on unsustainable groundwater use. Key Points: In 2012, 34.8 km 3 of depleted groundwater was transferred domestically and 3.7 km 3 was exported The mass of agricultural goods reliant on unsustainable groundwater in national and international supply chains decreased The value of agricultural goods reliant on groundwater depletion in national (54%) and international (31%) supply chains increased